2009
DOI: 10.1021/es900819t
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characteristics and Oxidative Potential of Particulate Matter Emissions from Gasoline, Diesel, and Biodiesel Cars

Abstract: Three light-duty vehicles in five different configurations [a Honda Accord operating with diesel with a closed-coupled oxidation catalyst and an underfloor catalyst replaced in some tests with a diesel particle filter (DPF), a Toyota Corolla operating with gasoline, and a VW Golf alternatively operating with petrodiesel or biodiesel] were tested in a dynamometer facility to develop an improved understanding of the factors affecting the toxicity of particulate exhaust emissions. The vehicles were tested using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
121
4
26

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(161 citation statements)
references
References 32 publications
10
121
4
26
Order By: Relevance
“…The volatile fraction and the growth of volatile fraction for 30 nm particles were the largest in almost all cases which showed that more attention is to be paid to smaller particles; not only because of their ability to suspend longer and penetrate deeper in the lung (Sidhu et al, 2001;Liu et al, 2008;Surawski et al, 2011;Cheung et al, 2009), but also because of their probability of carrying more oxidized volatile organics as they age.…”
Section: Volatility Measurementsmentioning
confidence: 98%
“…The volatile fraction and the growth of volatile fraction for 30 nm particles were the largest in almost all cases which showed that more attention is to be paid to smaller particles; not only because of their ability to suspend longer and penetrate deeper in the lung (Sidhu et al, 2001;Liu et al, 2008;Surawski et al, 2011;Cheung et al, 2009), but also because of their probability of carrying more oxidized volatile organics as they age.…”
Section: Volatility Measurementsmentioning
confidence: 98%
“…Cadle et al, 2009;Cheung et al, 2009;Geller et al, 2006;Kirchstetter et al, 1999;Liu et al, 2009;Subramanian et al, 2009;Yanowitz et al, 2000). For all world regions we assume that a certain fraction of vehicles is badly maintained (e.g.…”
Section: Transportmentioning
confidence: 99%
“…Toxicological studies are more frequent but focus mainly on laboratory-generated particles. Biswas et al (2009) reported a high oxidative potential for watersoluble OC emitted by heavy-duty engines, while Cheung et al (2009) showed an association of oxidative potential with water-soluble and water-insoluble OC in diesel engine emissions. A cytotoxic response was observed for organic nanoparticles generated by laboratory flame and by diesel engines (Manzo et al, 2010;Sgro et al, 2009).…”
Section: Particulate Matter and Healthmentioning
confidence: 99%